Kebijakan Madrasah Dalam Pembentukan Karakter Siswa Di MTsS Sirajul Huda Marindi - Chairul Echwan (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2025)
MTsS Sirajul Huda Marindi has a madrasah policy in shaping student character through activities oriented towards religious activities and other activities intended to shape student character. This study aims to determine the madrasah policy in shaping student character along with the supporting and inhibiting factors faced. This type of research is field research using qualitative descriptive methods. The subjects of this study were the Principal of MTsS Sirajul Huda Marindi, the Deputy Head of Student Affairs and the Teachers Council. Data collection techniques in this study were obtained from the results of observations, interviews and documentation. Data analysis techniques used range from data reduction, data display and data verification. The results of this study are that at the agenda preparation stage, a policy is issued by creating a program of activities related to improving student character and discussed in meetings. Then at the policy formulation stage, the program is discussed by policy makers. Furthermore, at the policy adoption stage, the policy program is approved with mutual support and agreement. It is implemented by instilling daily habits for students in the madrasah environment that are oriented towards religious activities and other activities. Finally, at the policy evaluation stage, evaluation meetings are regularly held. A supporting factor is the strong cooperation between teachers and educational staff at every stage of madrasah policy implementation. Meanwhile, a hindering factor is the problem faced by some students due to broken homes and the lack of parental supervision and guidance at home.